TINJAUAN KORELASI ANTARA KEMAMPUAN KONEKSI MATEMATIS DAN SELF-REGULATED LEARNING MATEMATIKA SISWA YANG PEMBELAJARANNYA MELALUI LEARNING CYCLE 5E - Sumarni Sumarni (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2016)
This article examines the crelation between mathematical connection ability and self-regulated learning (SRL) mathematics students through the Learning Cycle 5E (LC 5E). In this case, the mathematical connection ability include aspects (1) Understanding the relationships between concepts or mathematical rules; (2) Implement the relationships between concepts or mathematical rules with topics other disciplines; and (3) Understanding the relationships between concepts or rules of mathematics with applications in everyday life. Indicators SRL mathematics include: (1) Demonstrate initiative in learning mathematics; (2) Diagnosing needs in learning mathematics; (3) Setting a target / goal of learning; (4) To monitor, regulate and control study; (5) Seeing difficulty as a challenge; (6) Utilize and search for relevant learning resources; (7) Choose and implement learning strategies; (8) Evaluate learning process and results; and (9) Self efficacy. LC 5E is a learning model that consists of five stages: (1) engagement, (2) exploration, (3) explanation, (4) elaboration, and (5) evaluation. This article is based on research conducted on 35 students of class VII one junior high school in West Bandung regency. The results show there is corelation between mathematical connection ability and SRL mathematics students. Students with high mathematical connection ability tend to have high SRL mathematics too and students with low mathematical connections ability tend to have low SRLmathematics too.Keywords: mathematical connection ability, self-regulated learning, learning cycle 5E